Pelatihan Pemasaran dan Penyusunan Business Plan pada Kelompok Sadar Wisata Danau Talang - Ahmad Hidayat; Ahmad Adhitya; Evan Riyadi; Noura Rizki; Nurfaizah Yastri; Daffa Naufa Rizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The tourism industry can be a solution to moving the regional economy and overcoming the problems of poverty in Indonesia, especially the West Sumatra area with its various natural tourism potentials. It has become one of the most vital sectors in the last five years. It is necessary to develop and utilize tourism resources effectively and efficiently to support the tourism industry. This activity aims to develop a marketing strategy in Talang Lake based on sustainable and eco-friendly tourism destination management. The activity was carried out in the Talang Lake Tourism Area, Solok Regency, in collaboration with its local Tourism Awareness Group. This activity was carried out by providing marketing training and preparing a business plan design attended by the local management of Talang Lake. The various parties such as the government, the community, and the private sector are needed.